1997
DOI: 10.1016/s0893-133x(97)00054-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Arginine Vasopressin Elevated in Patients with Major Depression

Abstract: Mentally healthy subjects show increased plasma concentrations of the neuropeptides, arginine vasopressin (AVP) and oxytocin (OT), under conditions of stress, but data are lacking about plasma concentrations of AVP and OT in patients with major depression. We thus assessed plasma concentrations of AVP and OT in patients with major depression (n = 52) and healthy controls (n = 37). Mean plasma AVP concentrations were higher in the group of depressed patients than in controls. A subgroup of 16 patients showed ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
159
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(174 citation statements)
references
References 44 publications
12
159
3
Order By: Relevance
“…In addition, a blunting of OT secretion may be functionally related to the loss of appetite and the reduction of libido in depressive illness. In contrast, no significant difference was found between mean plasma levels of OT in depressed patients (N ¼ 52) and controls (N ¼ 37) by van Londen et al (1997), but Andeberg and Uvnas-Moberg (2000) reported a negative correlation between the levels of OT and the symptom scores of anxiety and depression in female fibromyalgia syndrome patients. In addition, a positive correlation has been found between the levels of OT and happiness.…”
Section: Article In Pressmentioning
confidence: 70%
“…In addition, a blunting of OT secretion may be functionally related to the loss of appetite and the reduction of libido in depressive illness. In contrast, no significant difference was found between mean plasma levels of OT in depressed patients (N ¼ 52) and controls (N ¼ 37) by van Londen et al (1997), but Andeberg and Uvnas-Moberg (2000) reported a negative correlation between the levels of OT and the symptom scores of anxiety and depression in female fibromyalgia syndrome patients. In addition, a positive correlation has been found between the levels of OT and happiness.…”
Section: Article In Pressmentioning
confidence: 70%
“…chronic mild stress as a model of depression (Duman, 2010, Yan et al, 2010, Overstreet, 2012) and the observed upregulation of AVP synthesis in parvocellular PVN neurons and V1b receptors at the anterior pituitary during chronic stress (Dallman, 1993, Aguilera et al, 1994 suggested the involvement of altered AVP signaling within the HPA axis in pathophysiological processes. Clinical studies found an increased AVP concentration in the cerebrospinal fluid (De Bellis et al, 1993, Heuser et al, 1998 and in the plasma (van Londen et al, 1997, van Londen et al, 1998, de Kloet et al, 2008 of depressive subjects, especially in suicide victims (Inder et al, 1997, Brunner et al, 2002. Postmortem studies have found an elevated number of AVP-expressing neurons, increased AVP level in the PVN (Purba et al, 1996, Merali et al, 2006 and an enhanced AVP mRNA You created this PDF from an application that is not licensed to print to novaPDF printer (http://www.novapdf.com) in the SON (Meynen et al, 2006).…”
mentioning
confidence: 99%
“…While the use of COX-2 inhibitors in association with reboxetine was found to increase symptomatological improvement in MDD patients [20], contrasting results have been reported regarding the potential role of OXT in depression [6,8,22,24,29]. This nonapeptide hormone has however been found to attenuate the stress response in both rats and humans [15].…”
Section: Bipolar Disordermentioning
confidence: 99%